2021
DOI: 10.1038/s41467-021-25423-8
|View full text |Cite|
|
Sign up to set email alerts
|

Intravital imaging of islet Ca2+ dynamics reveals enhanced β cell connectivity after bariatric surgery in mice

Abstract: Bariatric surgery improves both insulin sensitivity and secretion and can induce diabetes remission. However, the mechanisms and time courses of these changes, particularly the impact on β cell function, are difficult to monitor directly. In this study, we investigated the effect of Vertical Sleeve Gastrectomy (VSG) on β cell function in vivo by imaging Ca2+ dynamics in islets engrafted into the anterior eye chamber. Mirroring its clinical utility, VSG in mice results in significantly improved glucose toleranc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 78 publications
8
14
0
Order By: Relevance
“…Values were then corrected for the fact that, in implanted islets, approximately 20% of the imaged islet cross-section is covered by blood vessels. Using this method, we were able to determine the presence of four types of calcium wave activity, in line with earlier studies (Akalestou et al, 2021): islets where we observed activity over 0-25% of corrected area were characterized as type 1, if 26-50% of the islet cross-section was active these were typical of type 2, if 51-75% of the cross-section was active islets displayed type 3 activity and lastly, type 4 activity was assigned to islets where 76-100% of the cross-section was active.…”
Section: Methodssupporting
confidence: 86%
See 2 more Smart Citations
“…Values were then corrected for the fact that, in implanted islets, approximately 20% of the imaged islet cross-section is covered by blood vessels. Using this method, we were able to determine the presence of four types of calcium wave activity, in line with earlier studies (Akalestou et al, 2021): islets where we observed activity over 0-25% of corrected area were characterized as type 1, if 26-50% of the islet cross-section was active these were typical of type 2, if 51-75% of the cross-section was active islets displayed type 3 activity and lastly, type 4 activity was assigned to islets where 76-100% of the cross-section was active.…”
Section: Methodssupporting
confidence: 86%
“…Islets from these mice were then isolated and used for implantation in the anterior chamber of the eye of WT acceptor mice. This platform supported longitudinal in vivo imaging of calcium responses as previously shown (Akalestou et al, 2021; Salem et al, 2019) at mildly elevated in vivo glucose levels. Experiments were carried out under both chow and HFHS diet conditions, with islet donors and islet acceptors matched for diet type.…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…Additionally, trying to decipher the effects of vertical sleeve gastrectomy (VSG) on beta cell function in obese mice, Akalestou et al. have shown that Ca 2+ dynamics as well as the number and strength of connections between beta cells increase within 8-10 weeks post-surgery, which could be attributed to the strong influence of GLP-1 on islet functioning ( 57 ). GLP-1 in physiological picomolar concentrations augments postprandial insulin secretion.…”
Section: Functional Implications Of Beta Cell Network Analysismentioning
confidence: 99%
“…Functional multicellular Ca 2+ -imaging was performed on isolated islets as previously described [ 17 ]. Correlation analyses were performed between beta-cell pairs and their extracted fluorescent Ca 2+ traces over time in each imaged islet in MATLAB using a custom-made script, as previously described [ 18 ].…”
Section: Methodsmentioning
confidence: 99%